Cranial window implantation on mouse cortex to study microvascular change induced by cocaine - Park, Kicheon; You, Jiang; Du, Congwu; Pan, Yingtian (Quantitative Imaging in Medicine and Surgery, 2014)
Cocaine-induced stroke is among the most serious medical complications associated with cocaine’s abuse. However, the extent to which chronic cocaine may induce silent microischemia predisposing the cerebral tissue to neurotoxicity has not been investigated; in part, because of limitations of current neuroimaging tools, that is, lack of high spatiotemporal resolution and sensitivity to simultaneously measure cerebral blood flow (CBF) in vessels of different calibers quantitatively and over a large field of view (FOV). Optical coherence tomography (OCT) technique allows us to image three dimensional (3D) cerebrovascular network (including artery, vein, and capillary), and provides high resolution angiography of the cerebral vasculature and quantitative CBF velocity (CBFv) within the individual vessels in the network. In order to monitor the neurovascular changes from an in vivo brain along with the chronic cocaine exposure, we have developed an approach of implanting a cranial window on mouse brain to achieve long-term cortical imaging. The cranial window was implanted on sensorimotor cortex area in two animal groups, i.e., control group [saline treatment, ~0.1 cc/10 g/day, intraperitoneal injection (i.p.)] and chronic cocaine group (cocaine treatment, 30 mg/kg/day i.p.). After implantation, the cortex of individual animal was periodically imaged by OCT and stereoscope to provide angiography and quantitative CBFv of the cerebral vascular network, as well as the surface imaging of the brain. We have observed vascular hemodynamic changes (i.e., CBFv changes) induced by the cranial preparation in both animal groups, including the inflammatory response of brain shortly after the surgery (i.e., 5 days) in the brain. Importantly, by comparing with the control animals, the surgical-related vascular physiology changes in the cortex can be calibrated, so that the cocaine-induced hemodynamic changes in the neurovasculature can be determined in the cocaine animals. Our results demonstrate that this methodology can be used to explore the neurovascular functional changes induced by the brain diseases such as drug addiction.